Linking Training And Intellectual Intelligence To Employee Performance: The Role Of Work Commitment - Andi Syahruddin Djamal (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines the influence of training and intellectual intelligence on the performance of personnel at the Southeast Sulawesi Regional Police's Directorate of Special Criminal Investigation (Ditreskrimsus) and assesses work commitment as a moderating variable in both relationships. Researchers used a quantitative approach with an explanatory design and collected data through a survey of one hundred and twenty-five personnel who met the research criteria. Researchers used a closed-ended questionnaire compiled from indicators from previous studies, then adapted it to the context of law enforcement organizations so that each statement was relevant to the respondents' work situations. Researchers measured responses using a five-point Likert scale from strongly disagree to strongly agree. Researchers analyzed the data using SEM PLS with SmartPLS through measurement of evaluation models to ensure the validity and reliability of indicators, then evaluated the structural model to test the strength and significance of the relationships between variables. The results of the analysis showed improved training performance, so that improved training quality was related to improvements in work methods, procedural accuracy, and consistency of task implementation. Intellectual intelligence also improved performance and made the largest contribution, so that the ability to understand information, analyze situations, and make work decisions became important determinants of the quality of results. Moderation testing showed that work commitment strengthened the influence of training on performance, because highly committed personnel were more disciplined in applying training materials in their daily work. Work commitment also strengthens the influence of intellectual intelligence on performance, as it encourages the use of optimal thinking skills to complete tasks and maintain work standards.